Dental professionals' use of personal protective equipment during COVID-19: a cross-sectional study in China - Wan, Qinjie; Han, Lei; Yang, Xin; Yu, Shaoling; Zheng, Xiaohong (Frontiers in Public Health, 2023)
Background Appropriate use of personal protective equipment (PPE) could significantly reduce the risk of viral transmission and infection. This study aimed to assess the use of PPE among dentists during the COVID-19 pandemic in China, explore its influencing factors, and provide some practical recommendations. Methods An online cross-sectional survey was conducted among 384 Chinese dentists in September 2022. The questionnaire comprised a series of questions about demographic characteristics, compliance with proper PPE use, personal barriers to use, and exposure risk estimation. Results Of the 384 respondents, 57.3% had unacceptable compliance with the proper use of PPE during COVID-19. Medical surgical mask is the most common for dental professionals to wear (93.8%), followed by goggles or face shield (63.8%), and isolation gown (53.1%). Unexpectedly, only 63.3% of respondents always change masks with guidelines. The condition for changing goggles/face shields and isolation gowns is even worse (45.6 and 37.0%, respectively). Visual barriers, physical discomfort, complex procedures, and heavy workload were the most common personal barriers to use. According to the results of Chi-square test and correlation analysis, PPE use compliance was associated with age, years of practice, medical institution type, and exposure risk estimation. Conclusion Chinese dental professionals need to improve their compliance with the proper use of PPE, especially those in the 31–40 age group, with 11–15 experience years and working in private dental clinics. Increasing compliance with PPE may be achieved by addressing personal barriers to use, human resource shortages, and perceptions of exposure risk.